Selected Examples of Obscure Narrators in Musnad Imam Ahmad Musnad Al-Qabail: Collecting and Investigating (Islamic Sciences Journal, 2023)
ABSTRACT           It is well- recognized for intellectuals that Sunnah is the second legislative source after the Holy Qur’an. Islamic nation is marked by its legislative system that follows and preserves what is left from its Prophet’s instructions. This study aims at highlighting obscure narrators in  Musnad of Imam Ahmad,  the Musnad of the tribes, by collecting the methods of each of selected hadiths in which there was a vagueness in order to enlighten the knowledge of the obscure narrator.
Keywords: Musnad, Tribes. Ahmed bin Hanbal, The obscure